How employees’ monitoring perceptions affects organizational trust : the moderating role of organizational justice - Sarra, Rossana (2016)
How should organizations react to nowadays working context? Should technologic innovations in terms of employees’ behaviour surveillance be embraced and adopted by companies? What could be the implications of these practices? This study, based on an input-process-output model, seeks to investigate how monitoring employees may affect their attitudes towards the organization, more in specific, the focus will be on one variable: workers’ trust towards the organization. The research further proposes to determine whether the four organizational justice constructs significantly moderate the relationship between perceived monitoring and organizational trust. This research applied a quantitative research method, consisting on the analysis of responses obtained to a previously developed survey. Regression analysis was used in order to understand the relationship between monitoring in the workplace and trust towards the organization and to clarify the role played by the four dimensions of organizational justice. Inconsistently with the hypotheses developed, the results indicate that monitoring employees cannot be considered a factor, which negatively impacts the trust towards the organization. Likewise, the organizational justice domain does not significantly moderate this relationship: the four different organizational justice constructs reported statistically insignificant scores of interaction on the main relationship. Finally, the implications of the results are discussed with respect to clarifying possible explanation for the obtained outcomes and propose solutions to improve future studies in this area.